IMPROVING THE ABILITY TO RECOGNIZE SYMBOLS NUMBERS 1–10 THROUGH THE MEDIA OF NUMBER CARDS FOR CHILDREN AGED 4-5 YEARS GROUP B KB PIONEER VILLAGE TOMPEGUNUNG - Isna, Rondhia (USN Kolaka, 2023)
One of the cognitive abilities possessed by children aged four to five years is the ability to recognize number symbols. The low ability of group B children of the Tompegunung Makmur Pioneer KB in identifying numbers was the reason why this study was carried out. Learning activities using number card media can help children become more proficient in recognizing number symbols from 1 to 10. This research aims to improve recognition of number symbols 1–10 using number card media in group B KB Perintis Tompegunung Makmur. This form of research is called classroom action research, and has two cycles. Group B students of KB Perintis Tompegunung Makmur were study participants. The results showed that during pre-action to cycle II, children's recognition of the number symbols 1–10 increased. Using learning exercises with number cards can improve the quality of learning to make it interesting and efficient